Analisis Resepsi Anggota Komunitas Cisc Mengenai Kanker Serviks dalam Program Hi,Doc! di O Channel - Kodrat Adi Randar; Heppy New Year Haloho (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The "Hi,Doc!" program on the O Channel station is one of the health-related television programs. The episode "Early Detection of Cervical Cancer" of "Hi,Doc!" informs viewers about cervical cancer, its causes, and its treatment. The purpose of this study was to determine how CISC members responded to the "Hi,Doc!" program's information about cervical cancer. Utilizing three categories of audience positions, namely the dominant hegemony position, the negotiation position, and the opposition position. This study employs a qualitative methodology, descriptive research, and the encoding-decoding theory of Stuart Hall. Researchers employ techniques for analyzing audience response. According to the results, acceptance of each piece of information described in the "Hi,Doc!" program, Early Detection of Cervical Cancer, varied. The position of dominant hegemony dominates the information regarding the IVA test and HPV test, pap smear, the relationship between adolescent promiscuity and cervical cancer, and the need for early detection of cervical cancer for disease diagnosis. Next, the negotiation will concentrate on information about cervical cancer, risk factors for women with cervical cancer, and healthy prevention tips.